La vie de Guinevere - Lafferty, Paula (Avalon Books, 2024)
After the sudden death of her boyfriend, Vera would have been happy to spend the rest of her days curiously unnoticeable, washing bed sheets and cleaning toilets in present day Glastonbury. But when the strange new guest at her hotel reveals himself to be Merlin and drags her back to seventh century Camelot, a place she knows only from legends, only Vera (or Queen Guinevere as Merlin calls her) can right the course of history and save Arthur' s kingdom from the will of a power-hungry mage. There' s one enormous problem: Guinevere was the sole witness to the curse that' s now draining the kingdom of its magic, and Vera doesn't remember anything of her supposed life as Queen Guinevere. With Camelot' s peace ebbing ever closer to shattering, the clock is ticking. But working with Merlin' s magic to retrieve her long-lost memories and save the kingdom brings more questions than answers: why is it that King Arthur, who treats his subjects with loving benevolence, can' t even stand to look at her? And why does that make Vera' s soul feel like it' s splitting in two? What robbed her of her memories in the first place... And most importantly... Why? As Vera is about to discover; in a world of legend and power, the secrets of her memories are only the beginning.